The Implementation of Cornell Note-Taking to Improving Students' Reading Comprehension - Siti Tri Ulfani; Listyaning Sumardiyani; Laily Nur Affini (Pusat Riset dan Inovasi Nasional, 2023)
The main objective of this study was to determine the significant difference in improving students' reading comprehension before and after being taught using the Cornell Note-Taking method. This type of research is quantitative research using a quasi-experimental research design. This study sampled 62 of 287 students. Researchers collected data with pre-and post-tests. The test is multiple-choice with recount text material. The analysis revealed a significant difference between the experimental and control classes. After using Cornell Note-Taking, the experimental class scored 61.03 on the pre-test and 76.52 on the post-test, a 15.49 increase. Without treatment, the control class scored 54.32 pre-test and 67.87 post-test, a 13.55 increase. Experimental class scores were higher. Meanwhile, through the Independent Samples T-test, the T-test sig. (2-tailed) shows 0.000 < 0.050, which means Ha is accepted and Ho is rejected. On the other hand, the result of the t-table test using a significance level of 5%, the resulting t-test value is greater than the t-table (5.410 > 1.670). The resulting p-value of 0.000 is smaller than the significance level of 0.050, so the results of applying the Cornell Note-Taking method are proven effective and can improve students' reading comprehension skills.